A theoretical study of taper characteristics to optimize performance - Thomas, L.; Busso, T. (Medicine & Science in Sports & Exercise, 2005)
Purpose: The aim of this study was to examine the training factors that could affect taper efficiency. The analysis was done using simulations from a nonlinear model of the training effects on performance giving an individual optimal daily training (ODT)